2004
DOI: 10.1029/2004jd004979
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for hygroscopic mineral dust particles from the Intercontinental Transport and Chemical Transformation Experiment

Abstract: [1] Two collocated, eight-stage rotating drum impactors were deployed at Trinidad Head (California) during the spring of 2002 as part of the Intercontinental Transport and Chemical Transformation 2002 (ITCT 2K2) experiment. One of the samplers operated at ambient relative humidity while the other was operated at a relative humidity of 55%. The impaction substrates from these samplers were analyzed using synchrotron X-ray fluorescence (SXRF) to provide continuous measurements of the size-resolved aerosol elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 40 publications
4
78
0
1
Order By: Relevance
“…Slope, intercept and correlation coefficient values of the linear fits can be found in Table 4. been shown to increase particle hygroscopicity (Perry et al, 2004;Furutani et al, 2008). Chilbolton, being a continental background site representative of the regional aerosol properties, also belongs to this group; however, the N CCN concentrations at this location may be underestimated due to the aerosol not being dried prior to entering the CCNC (Whitehead et al, 2014).…”
Section: Ccn Concentrationsmentioning
confidence: 99%
“…Slope, intercept and correlation coefficient values of the linear fits can be found in Table 4. been shown to increase particle hygroscopicity (Perry et al, 2004;Furutani et al, 2008). Chilbolton, being a continental background site representative of the regional aerosol properties, also belongs to this group; however, the N CCN concentrations at this location may be underestimated due to the aerosol not being dried prior to entering the CCNC (Whitehead et al, 2014).…”
Section: Ccn Concentrationsmentioning
confidence: 99%
“…Hand and Malm (2006) indicated that the scattering coefficients of (NH 4 ) 2 SO 4 and (NH 4 )HSO 4 aerosols could be enhanced by a factor of three when relative humidity is over 85%. Dust particles, dominant in coarse mode, are mostly insoluble with f (RH=80%) smaller than 1.1 (Li-Jones et al, 1998), but they could also be hygroscopic when coated by sulfate or other soluble inorganic aerosols during transportation (Perry et al, 2004;Shi et al, 2007). During the period of Aerosol Characterization Experiment (ACE-Asia), dust particle's hygroscopic factor of f (RH=80%)=1.25 was observed in Ron Brown cruise (Carrico et al, 2003), and even as high as 2.0 in Korea (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Observations show that secondary aerosol species such as sulfate and nitrate often exist as surface coatings on Asian dust as a result of these processes (Mori et al, 2003;Ooki and Uematsu, 2005;Perry et al, 2004;Tang et al, 2004a, b;Trochkine et al, 2003;Xiao et al, 1997;Zhang et al, 2000;Sullivan et al, 2007;Matsuki et al, 2005a, b). The presence of this material can enhance the solubility of dust particles, increasing their ability to act as cloud drop or ice immersion nuclei (Perry et al, 2004), and can increase the bioavailability of iron, which enhances the fertilisation of marine phytoplankton (Jickells et al, 2005;Meskhidze et al, 2003Meskhidze et al, , 2005. A further consequence of the uptake of secondary aerosol material, considered in this study, is that existing aerosol could be affected by dust via reduced concentrations of aerosol precursor gases, thereby influencing existing particle concentrations and even cloud condensation nuclei by reduced growth and new particle formation.…”
Section: Introductionmentioning
confidence: 99%